Determinants of Customer Retention in Cellular Industry of Bangladesh: A Study on Young Customers - Md. Bazlur Rahman; Newma Chowdhury (Indonesian Journal of Social Research (IJSR), 2022)
The telecommunication industry in Bangladesh, with the global trends, has been considerably grown up during the last two decades. At the end of December 2020, the number of cellular phone subscribers reached 170.137 million under four operators in the country. The telecommunication industry has been experiencing increased competition because the government has introduced uniform call rates for all operators and launched mobile number portability (MNP) in 2018, resulting in an easy switching for a customer to other operators. This situation has originated a great challenge for the cellular service providers in Bangladesh to retain the existing customers, especially the young subscribers who have more switching trends. The hyper-competition in the industry also induced mobile operators to work hard to attract new customers and retain the existing ones. The paper, therefore, aims to find out the determinants of young customer retention in the cellular industry of Bangladesh. This study is exploratory based on primary data collected from 415 young cellular phone users of the age of below 40 years in the two largest cities (Dhaka and Chittagong) in Bangladesh. The study examined eight determining factors of customer retention using the statistical tools: mean and standard deviation. The study found that price perception, customer satisfaction, switching barriers, and brand image are the strongest customer retention determinants. This study's findings have important implications for cellular phone operators to tailor their services and strategic priorities for maximizing customer satisfaction, loyalty, and retention to gain market growth and higher returns.